2016
DOI: 10.1016/j.apgeog.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Scale effects in food environment research: Implications from assessing socioeconomic dimensions of supermarket accessibility in an eight-county region of South Carolina

Abstract: Choice of neighborhood scale affects associations between environmental attributes and health-related outcomes. This phenomenon, a part of the modifiable areal unit problem, has been described fully in geography but not as it relates to food environment research. Using two administrative-based geographic boundaries (census tracts and block groups), supermarket geographic measures (density, cumulative opportunity and distance to nearest) were created to examine differences by scale and associations between thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 53 publications
0
14
1
Order By: Relevance
“…These small shops also provide the additional advantage of providing a livelihood for an estimated one in fifty households. Unlike the context for most other food desert studies to date (Jiao et al 2012;Frndak 2014;USDA 2015;Barnes et al 2016), large supermarket chains are yet to dominate the food market in this transitioning economy and thus have not had the impact seen elsewhere of outcompeting local neighborhood shops (Cummins and McIntyre 2002;Gartin 2012). Our results show, however, that in areas with lower income poverty, the overall density of shops is lower, whereas the facilities offered by stores are higher.…”
Section: Presence Of Food Desertscontrasting
confidence: 63%
“…These small shops also provide the additional advantage of providing a livelihood for an estimated one in fifty households. Unlike the context for most other food desert studies to date (Jiao et al 2012;Frndak 2014;USDA 2015;Barnes et al 2016), large supermarket chains are yet to dominate the food market in this transitioning economy and thus have not had the impact seen elsewhere of outcompeting local neighborhood shops (Cummins and McIntyre 2002;Gartin 2012). Our results show, however, that in areas with lower income poverty, the overall density of shops is lower, whereas the facilities offered by stores are higher.…”
Section: Presence Of Food Desertscontrasting
confidence: 63%
“…Further, maternal address at the time of delivery was used as a proxy for address during pregnancy, but this does not take into account moving patterns. 26 Similarly, the USDA Food Access Research Atlas used supermarket data from 2006 to 2010 and census data from 2010, and we studied births from 2010 to 2014. Clinical data from 2010 to 2014 were chosen for this analysis as they were the most contemporary data available for Chicago and thus the most generalizable to current populations, yet it is possible that areas considered food deserts in 2010 experienced gentrification or construction of a new grocery store by 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Within-study comparisons of standardised β regression coefficients have not been reported in earlier reviews of this nature, and our review is the first to our knowledge to compare within-study effect sizes of different measures of spatial exposure to food outlets. When comparing within-study effects, this review accounted for the scale at which availability measures were derived (i.e., differing buffer sizes) as previous work has indicted the presence of potential scale effects on exposure measures [ 71 , 72 ]. Previous reviews examining the CFE-diet relationship have not stratified their findings by scale.…”
Section: Discussionmentioning
confidence: 99%